Residual strain orientation in rolled titanium determined with synchrotron X‐ray Laue microdiffraction. Issue 1 (9th January 2023) - Devoe, Michelle; Tamura, Nobumichi; Wenk, Hans-Rudolf
Abstract : Synchrotron X‐ray Laue microdiffraction is used to measure the residual stress in rolled titanium, a metal with known deformation history, and determine the orientation of the residual stress ellipsoid. Previously the method has only been used on naturally deformed quartzites with ambiguous deformation histories. Abstract : Previously, synchrotron X‐ray Laue microdiffraction has been used to measure the magnitudes of residual strain in materials. Recently the method was advanced to determine the orientation of the strain ellipsoid and applied to naturally deformed quartzites; however, the deformation history of these quartzites is ambiguous due to their natural origin. In this study, synchrotron X‐ray Laue microdiffraction (µXRD) is used to measure the residual strain for the first time in a sample with known stress history, rolled titanium. A deviatoric strain tensor is calculated from each Laue diffraction image collected with two µXRD scans of a rolled titanium sheet in different sample orientations. The principal strain axes are calculated using an eigen decomposition of the deviatoric strain tensors. The results show that the principal axis of compression is aligned with the normal direction of the titanium sheet, and the principal axis of extension is aligned with the rolling direction. Pole figures are used to represent the 3D distribution of residual strain axes.